Implementation of Information and Communication Technologies in Test Control of Leg Strength in Physical Education of Students - Oksana Blavt; Gennadii Iedynak; Maryan Pityn; Ivan Hlukhov; Michajlo Guska; Volodymyr Stadnyk; Andriy Zaikin; Ivan Karatnyk (OVS LLC, 2022)
The purpose of this study was to experimentally substantiate the implementation of information and communication technologies in test control of leg strength in the process of physical education of students. Materials and methods. The methods used to obtain empirical data included pedagogical experiment, pedagogical testing, mathematical methods for processing digital files, comparative statistical method, variance and correlation analysis. The study participants were 240 students aged 17-19 at the beginning of the study. Results. A developed device for determining leg muscle strength, built based on the latest information and communication technologies, was presented. The developed design of the device involves the use of analog laser distance sensors the information from which is sent to the processing unit via wireless infrared communication devices and fed to the electronic computing device through an analog-to-digital converter. By calculating the authenticity of the test exercise used to control leg strength, the use of the developed device in practical activities was experimentally substantiated. According to the results of the correlation analysis, it was established that the authenticity of control using the developed device has reached a high level. Conclusions. A qualitatively new approach to increasing the effectiveness of control in physical education of students was presented, which is implemented in the developed leg strength control device. The applied value of the results of the conducted research is that the device developed based on information and communication technologies provides a qualitatively new form of implementation of leg force control as well as processing and presentation of control information. The use of the device in the practice of physical education of students ensures the effectiveness and high efficiency of the control procedure, the result of which is the receipt of reliable data, which makes it possible to significantly improve the quality and intensify control of this process to ensure the effectiveness of physical education of students.